Cultural determinants of the masculine gender role transformation. Women's and men's assessment of the traditional and non-traditional masculinity model in perceived reflected-appraisals perspective - Agnieszka Nowakowska-Kaliszuk (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
Critical gender studies indicate the dysfunctionality of the traditional masculinity model, both in the emotional and health spheres. However, the implementation of the non-traditional model by men enables a deeper involvement in fatherhood, emotional development and partnership (instead of domination). Numerous studies indicate that men take on non-traditional gender roles because of the assessment of others, not just their own beliefs. The aim of the present study among young Polish men (N = 351) was to verify their evaluation of the traditional and non-traditional masculinity model. The assessment is expressed here through individual declarations, as well as an idea of the assessment given to a presented model by women and other men. The results indicate higher preferences of the non-traditional male model than the traditional one. Participants estimate that the non-traditional model is rated higher by women and traditional by other men. Awareness of women's assessment (perceived reflected-appraisals) is a factor encouraging the imitation of a given masculinity model.